Drivers of Land Degradation and Policy Implications of Taking Action - Mirzabaev, Alisher (2015)
IFPRI Policy Seminar “Economics of Land Degradation and Improvement--A Global Assessment for Sustainable Development” held on December 3, 2015. Presentation by Alisher Mirzabaev, Center for Development Research (ZEF), University of Bonn.